Angiographic control versus ischaemia-driven management of patients undergoing percutaneous revascularisation of the unprotected left main coronary artery with second-generation drug-eluting stents: rationale and design of the PULSE trial. Issue 2 (29th October 2020) - De Filippo, Ovidio; Bianco, Matteo; Tebaldi, Matteo; Iannaccone, Mario; Gaido, Luca; Guiducci, Vincenzo; Santarelli, Andrea; Zaccaro, Lorenzo; Depaoli, Alessandro; Vaudano, Paolo; Quadri, Giorgio; Gagnor, Andrea; et al.
Abstract : Background: The role of planned angiographic control (PAC) over a conservative management driven by symptoms and ischaemia following percutaneous coronary intervention (PCI) of the unprotected left main (ULM) with second-generation drug-eluting stents remains controversial. PAC may timely detect intrastent restenosis, but it is still unclear if this translated into improved prognosis. Methods and analysis: PULSE is a prospective, multicentre, open-label, randomised controlled trial. Consecutive patients treated with PCI on ULM will be included, and after the index revascularisation patients will be randomised to PAC strategy performed with CT coronary after 6 months versus a conservative symptoms and ischaemia-driven follow-up management. Follow-up will be for at least 18 months from randomisation. Major adverse cardiovascular events at 18 months (a composite endpoint including death, cardiovascular death, myocardial infarction (MI) (excluding periprocedural MI), unstable angina, stent thrombosis) will be the primary efficacy outcome. Secondary outcomes will include any unplanned target lesion revascularisation (TLR) and TLR driven by PAC. Safety endpoints embrace worsening of renal failure and bleeding events. A sample size of 550 patients (275 per group) is required to have a 80% chance of detecting, as significant at the 5% level, a 7.5% relative reduction in the primary outcome. Trial registration number: NCT04144881